Evaluation of yield stability of cowpea under sole and intercrop management in Nigeria - Blade, S.; Mather, D.; Singh, B.; Smith, D. (1992)
Nine cowpea (Vigna unguiculata (L.) Walp.) breeding lines were grown in 13 experiments under sole crop and intercrop management, with and without insecticide application, in Nigeria. Cowpea was intercropped with cassava (Manihot esculenta Cranz), maize (Zea mays L.) and maize-cassava in the forest zone and with sorghum (Sorghum bicolor Moench.) and millet (Pennisetum glaucum (L.) R.Br.) in the savanna zone. Line by cropping system interactions were significant in 5 of 13 experiments and line by insecticide treatment interactions were significant in 2 of 13 experiments. Cowpea yield was severely depressed in intercropped plots and in plots to which no insecticide was applied. Among-environment variation in cowpea yield was greater when no insecticide was applied. Within each management treatment, the yield performance and stability of the cowpea lines was examined. Stability was assessed both by examining among-environment coefficients of variation and by regression analysis. Several of the breeding lines evaluated appeared promising under different levels of management and in a diversity of environments.